Morality, Deviance, and Regulation: Pragmatist Motifs in Plato's "Republic" and "Laws" - Prus, Robert (Qualitative Sociology Review, 2011)
Envisioning morality, deviance, and regulation as enduring features of human group life, and using symbolic interaction (Mead 1934; Blumer 1969; Prus 1996; Prus and Grills 2003) as a conceptual device for traversing the corridors of time, this paper asks what we may learn about deviance and morality as humanly engaged realms of community life by examining Plato's (420-348 BCE) Republic and Laws. Focusing on the articulation of two model communities, with Republic primarily under the guidance of a set of philosopher-kings and Laws more comprehensively under the rule of a constitution, Plato considers a wide array of matters pertinent to the study of morality, deviance, and regulation. Thus, whereas many social scientists have dismissed Plato's texts as the works of a “utopian idealist” and/or an “ancient philosopher,” Republic and Laws have much to offer to those who approach the study of human knowing and acting in more distinctively pragmatist sociological terms. Indeed, because these two volumes address so many basic features of community life (including morality, religion, politics, poetics, and education) in extended detail, they represent particularly valuable transhistorical and transcultural comparison points for contemporary analysis. Although the products of a somewhat unique period in Western civilization (i.e., the classical Greek era, circa 700-300 BCE), Plato's Republic and Laws are very much studies of social order. Plato's speakers, in each case, clearly have notions of the moral order that they wish to promote, but, to their sociological credit, they also embark on more distinctively analytic considerations of the broader processes and problematics of humanly engaged life worlds. Still, given the practical restraints of a single paper and the extended relevance of Plato's texts for the topics at hand, readers are cautioned that the present statement focuses primarily on those materials from Republic that most directly address deviance and regulation and mainly the first six books of Laws. Employing Prus and Grills (2003) depictions of deviance as a series of generic social processes as a contemporary reference point, the paper concludes with a consideration of the relevance and contributions of Plato's Republic and Laws for the study of morality, deviance, and regulation as fundamental features of human group life.